FIGURES OF SPEECH REFLECTING LOATHING - Ambalegin Ambalegin; Tomi Arianto (Universitas Putera Batam, 2020)
This descriptive qualitative research identified briefly the figurative expressions on Donald Trump’s tweeter post. It used Abrams and Harpham’s theory. This research applied observational method and non-participation technique in collecting the data. Then, this research applied semantic identity method and semantic-competence in equalizing to analyze the data. The figure of similarity found mostly in the comments or responses. There were expressions of simile, metaphor, allusion, and personification. The comments or responses mostly compared the one to the other living or non-living things to express how loathe the writers of comments. The figures of speech criticized the one’s works and acts. On the other hand, the expressions attacked the face (FTA). Previously, the figures of speech were used in the literary works to show the expression aesthetically. But now, the freedom to express the ideas makes the figures of speech not only to show the ‘sweet and smooth’ language but also ‘rude’ language.